Medical interventions for the prevention of platinum‐induced hearing loss in children with cancer - van As, Jorrit W (Cochrane Database Syst Rev, 2019)
BACKGROUND: Platinum‐based therapy, including cisplatin, carboplatin, oxaliplatin or a combination of these, is used to treat a variety of paediatric malignancies. One of the most significant adverse effects is the occurrence of hearing loss or ototoxicity. In an effort to prevent this ototoxicity, different otoprotective medical interventions have been studied. This review is the third update of a previously published Cochrane Review. OBJECTIVES: To assess the efficacy of medical interventions to prevent hearing loss and to determine possible effects of these interventions on antitumour efficacy, toxicities other than hearing loss and quality of life in children with cancer treated with platinum‐based therapy as compared to placebo, no additional treatment or another protective medical intervention. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials, MEDLINE (PubMed) and Embase (Ovid) to 8 January 2019. We handsearched reference lists of relevant articles and assessed the conference proceedings of the International Society for Paediatric Oncology (2006 up to and including 2018), the American Society of Pediatric Hematology/Oncology (2007 up to and including 2018) and the International Conference on Long‐Term Complications of Treatment of Children and Adolescents for Cancer (2010 up to and including 2015). We scanned ClinicalTrials.gov and the World Health Organization International Clinical Trials Registry Platform (WHO ICTRP; apps.who.int/trialsearch) for ongoing trials (on 2 January 2019). SELECTION CRITERIA: Randomized controlled trials (RCTs) or controlled clinical trials (CCTs) evaluating platinum‐based therapy with an otoprotective medical intervention versus platinum‐based therapy with placebo, no additional treatment or another protective medical intervention in children with cancer. DATA COLLECTION AND ANALYSIS: Two review authors independently performed the study selection, data extraction, risk of bias assessment and GRADE assessment of included studies, including adverse effects. We performed analyses according to the Cochrane Handbook for Systematic Reviews of Interventions. MAIN RESULTS: We identified two RCTs and one CCT (total number of participants 149) evaluating the use of amifostine versus no additional treatment in the original version of the review; the updates identified no additional studies. Two studies included children with osteosarcoma, and the other study included children with hepatoblastoma. Children received cisplatin only or a combination of cisplatin and carboplatin, either intra‐arterially or intravenously. Pooling of results of the included studies was not possible. From individual studies the effect of amifostine on symptomatic ototoxicity only (i.e. National Cancer Institute Common Toxicity Criteria version 2 (NCICTCv2) or modified Brock grade 2 or higher) and combined asymptomatic and symptomatic ototoxicity (i.e. NCICTCv2 or modified Brock grade 1 or higher) were uncertain (low‐certainty evidence). Only one study including children with osteosarcoma treated with intra‐arterial cisplatin provided information on tumour response, defined as the number of participants with a good or partial remission. The available‐data analysis (data were missing for one participant), best‐case scenario analysis and worst‐case scenario analysis showed a difference in favour of amifostine, although the certainty of evidence for this effect was low. There was no information on survival for any of the included studies. Only one study, including children with osteosarcoma treated with intra‐arterial cisplatin, provided data on the number of participants with adverse effects other than ototoxicity grade 3 or higher (on NCICTCv2 scale). There was low‐certainty evidence that grade 3 or 4 vomiting was higher with amifostine (risk ratio (RR) 9.04, 95% confidence interval (CI) 1.99 to 41.12). The effects on cardiotoxicity and renal toxicity grade 3 or 4 were uncertain (low‐certainty evidence). None of the studies evaluated quality of life. In the recent update, we also identified one RCT including 109 children with localized hepatoblastoma evaluating the use of sodium thiosulfate versus no additional treatment. Children received intravenous cisplatin only (one child also received carboplatin). There was moderate‐certainty evidence that both symptomatic ototoxicity only (i.e. Brock criteria grade 2 or higher) and combined asymptomatic and symptomatic ototoxicity (i.e. Brock criteria grade 1 or higher) was lower with sodium thiosulfate (combined asymptomatic and symptomatic ototoxicity: RR 0.52, 95% CI 0.33 to 0.81; symptomatic ototoxicity only: RR 0.39, 95% CI 0.19 to 0.83). The effect of sodium thiosulfate on tumour response (defined as number of participants with a complete or partial response at the end of treatment), overall survival (calculated from time of randomization to death or last follow‐up), event‐free survival (calculated from time of randomization until disease progression, disease relapse, second primary cancer, death, or last follow‐up, whichever came first) and adverse effects other than hearing loss and tinnitus grade 3 or higher (according to National Cancer Institute Common Toxicity Criteria Adverse Effects version 3 (NCICTCAEv3) criteria) was uncertain (low‐certainty evidence for all these outcomes). Quality of life was not assessed. We found no eligible studies for possible otoprotective medical interventions other than amifostine and sodium thiosulfate and for other types of malignancies. AUTHORS' CONCLUSIONS: At the moment there is no evidence from individual studies in children with osteosarcoma or hepatoblastoma treated with different platinum analogues and dosage schedules that underscores the use of amifostine as an otoprotective intervention as compared to no additional treatment. Since pooling of results was not possible and the evidence was of low certainty, no definitive conclusions can be made. Since we found only one RCT evaluating the use of sodium thiosulfate in children with localized hepatoblastoma treated with cisplatin, no definitive conclusions on benefits and harms can be drawn. It should be noted that 'no evidence of effect', as identified in this review, is not the same as 'evidence of no effect'. We identified no eligible studies for other possible otoprotective medical interventions and other types of malignancies, so no conclusions can be made about their efficacy in preventing ototoxicity in children treated with platinum‐based therapy. More high‐quality research is needed.